The Application of Due Process of Law in Cyberbullying Crimes Comitted by Children at the Investigation Stage - Hidaya, Nada Ramadan Umul; Ibrahim, Septi Maulana Malik; Wicaksana, Subandito Adi; Henda, Raden; Umar, Jaenudin (Journal of Legal and Cultural Analytics, 2025)
This study examines the application of due process of law in cyberbullying cases committed by children at the investigation stage. Using a normative juridical method, the paper evaluates the legal protection framework, particularly in the absence of specific cyberbullying regulations. Key findings reveal legal uncertainty, lack of digital evidence capacity among law enforcement, and the use of cumulative charges ignoring restorative justice principles. The study contributes to legal scholarship by emphasizing the need for regulatory harmonization and increased competence in handling digital crimes, advocating for a child-centered approach to justice in the digital era.